1999
DOI: 10.2135/cropsci1999.0011183x003900030019x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Wheat Senescence with a Digital Camera

Abstract: Documenting crop senescence rates is often difficult because of the need for frequent sampling during periods of rapid change and the subjective nature of human visual observations. The purpose of this study was to determine the feasibility of using images produced by a digital camera to measure the senescence rate of wheat and to compare the results with changes in greenness determined by two established methods. Measurements were made as part of an experiment to determine the effects of elevated C02 and limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
140
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(151 citation statements)
references
References 0 publications
3
140
0
8
Order By: Relevance
“…Adamsen et al (1999) were some of the earliest users of digital cameras, and they examined senescence in a wheat canopy over 1-m 2 areas by using a ratio of green to red pixel values. Lukina et al (1999) used digital images to estimate the vegetation coverage and biomass of wheat, and Purcel (2000) compared captured images with under-canopy measurements of light for estimating total ground cover of soybean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adamsen et al (1999) were some of the earliest users of digital cameras, and they examined senescence in a wheat canopy over 1-m 2 areas by using a ratio of green to red pixel values. Lukina et al (1999) used digital images to estimate the vegetation coverage and biomass of wheat, and Purcel (2000) compared captured images with under-canopy measurements of light for estimating total ground cover of soybean.…”
Section: Introductionmentioning
confidence: 99%
“…The color index of green : red ratio (Adamsen et al 1999) chosen for this study provided the best signal of color change in the field compared to several other methods investigated. Total reflectivity was not considered a good index because dead samples also increased in reflectivity upon hydration.…”
mentioning
confidence: 99%
“…Recently, the feasibility of using single-lens refl ex digital cameras for mapping was reported (Kunii and Murai, 2008). In fact, several authors have shown favorable results using color video or still digital cameras, or multiband cameras equipped with a near infrared band-pass fi lter for assessing crop coverage or leaf greenness (e.g., Kawashima and Nakatani, 1998;Adamsen et al, 1999;Purcell, 2000;Zhou and Robson, 2001;Matsuda et al, 2003;Jia et al, 2004;Ku et al, 2004;Casadesus et al, 2007;Omine, 2007;Takemine et al, 2007;Crimmins and Crimmins, 2008;Okada and Ikeba, 2008;Takada et al, 2009;Sakamoto et al, 2010).…”
mentioning
confidence: 99%
“…Color analysis is used to study plant cells or biological products in such widely varied plant systems as wheat senescence (Adamsen et al, 1999) and fruit grading to determine picking time for apples (Schrevens and Raeymaeckers, 1992).…”
Section: Introductionmentioning
confidence: 99%